Seccesion and self-determination in small Caribbean states : Nevis - Premdas, Ralph (UWI St. AugustineTT, 1998)
Explores the issues, problems and prospects of Nevis seccesion from St. Kitts. Engages the discussion within the wider framework of the origins of the teritorial state and looks at theoretical and historical issues related to self-determination.